FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NON MUSLIM MENJADI NASABAH BANK SYARIAH DI TASIKMALAYA - Lina Marlina (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
This research is intended to find out what factors are causing non-Muslims to become customers of Islamic banks. The study was conducted at the BNI Syariah branch of Tasikmalaya. The method used in this research is quantitative research methods. The results of the study show that: (1) Location partially does not affect the interest of non-Muslims to become customers at BNI Syariah Tasikmalaya Branch. This is indicated by the t test which obtained the value of tcount <ttable (1.090 <1.657); (2) Service partially has no effect on the interest of non-Muslims being customers at BNI Syariah Tasikmalaya Branch. This is indicated by the t test obtained -count> -table (-1,055> -1,657). 3. Religious stimuli partially has no effect on the interest of non-Muslims becoming customers at BNI Syariah Tasikmalaya Branch. This is indicated by the t test which obtained the value of -count> -table (-0.586> -1.657); (3) Reputation Partially does not affect the interest of non-Muslims to become customers at BNI Syariah Tasikmalaya Branch. This is indicated by the t test which obtained the value of -count> -table (-0.448> 1.657); (4) Profit sharing Partially has no effect on the interest of non-Muslims becoming customers at BNI Syariah Tasikmalaya Branch. This is indicated by the t test which obtained the value of -count> -table (-0.630> -1.657); (5) Promotion partially affects the interest of non-Muslims being customers at BNI Syariah Tasikmalaya Branch. This is indicated by the t test obtained t value> t table (2.571> 1.657); (6) Location, service, religious stimuli, reputation, profit sharing, and promotion simultaneously do not affect the interest of non-Muslims to become customers at BNI Syariah Tasikmalaya Branch. This is indicated by the F test which obtained the calculated F value <F table (1.619 <2.17).